Age-related changes in salivary biomarkers - Mohannad Nassar; Noriko Hiraishi; Md. Sofiqul Islam; Masayuki Otsuki; Junji Tagami (Elsevier, 2014)
Background/purpose: Saliva plays a critical role in the oral cavity health; the levels of its constituents alter with age. The reduced glutathione:oxidized glutathione ratio (GSH:GSSG) in the plasma is reported to be lower in elderly people and thus can be an indicator of age. The aim of this study was to detect age-related changes in salivary biomarker levels and evaluate whether the salivary GSH:GSSG ratio can be an indicator of aging. Materials and methods: Individuals who participated in this study were divided into two groups: the elderly group (n = 20; age 60-80 years) and the young group (n = 20; age 20-30 years). Unstimulated saliva was collected passively for 5 minutes, followed by clinical examination. The salivary flow rate (SFR), pH, and buffering capacity were measured, followed by centrifugation of saliva, collection of supernatant, and measurement of the following biomarkers: calcium (Ca), alpha (α)-amylase, GSH, GSSG, matrix metalloproteinase-8 (MMP-8), collagenase type-I, and tissue inhibitor of metalloproteinase (TIMP-1). Descriptive analyses of variables were performed. Results: The elderly group showed significantly lower SFR and Ca than the young group, whereas collagenase type-1 and MMP-8 were significantly lower in the young group. None of pH, buffering capacity, α-amylase, GSH, GSSG, GSH:GSSG, or TIMP-1 showed any statistically significant difference between the two groups. Conclusion: Saliva is a mixture of components, the levels of which can increase, decrease, or remain stable with age. Although the GSH:GSSG ratio was lower in the elderly group, it did not reach a level of significance.